Functionality of Immunoglobulin G and Immunoglobulin M Antibody Physisorbed on Cellulosic Films - Huang, Ziwei; Raghuwanshi, Vikram Singh; Garnier, Gil (Frontiers in Bioengineering and Biotechnology, 2017)
The functionality and aging mechanism of antibodies physisorbed onto cellulosic films was investigated. Blood grouping antibodies immunoglobulin G (IgG) and immunoglobulin M (IgM) were adsorbed onto smooth cellulose acetate (CAF) and regenerated cellulose (RCF) films. Cellulose films and adsorbed IgG layers were characterized at the air and liquid interface by X-ray and neutron reflectivity (NR), respectively. Cellulose film 208 Å thick (in air) swell to 386 Å once equilibrated in water. IgG adsorbs from solution onto cellulose as a partial layer 62 Å thick. IgG and IgM antibodies were adsorbed onto cellulose and cellulose acetate films, air dried and aged at room temperature for periods up to 20 days. Antibody functionality and surface hydrophobicity were measured everyday with the size of red blood cell (RBC) agglutinates (using RBC specific to IgG/IgM) and the water droplet contact angle, respectively. The functionality of the aged IgG/IgM decreases faster if physisorbed on cellulose than on cellulose acetate and correlates to surface hydrophobicity. IgG physisorbed on RCF or CAF age better and remain functional longer than physisorbed IgM. We found a correlation between antibody stability and hydrogen bond formation ability of the system, evaluated from antibody carbonyl concentration and cellulosic surface hydroxyl concentration. Antibody physisorbs on cellulose by weak dipole forces and hydrogen bonds. Strong hydrogen bonding contributes to the physisorption of antibody on cellulose into a non-functional configuration in which the molecule relaxes by rotation of hydophobic groups toward the air interface.